Front Cover Picture: Enantioselective Iodine(I/III) Catalysis in Organic Synthesis (Adv. Synth. Catal. 1/2019). Issue 1 (16th November 2018) - Flores, Andrea; Cots, Eric; Bergès, Julien; Muñiz, Kilian
Abstract : The front cover picture is provided by Kilian Muñiz and co‐workers. "How would you like to live in Looking‐Glass House, Kitty? I wonder if they′d give you milk in there? Perhaps Looking‐Glass milk isn′t good to drink?" Alice's questions from the famous book from Lewis Carroll correlate to the expanding wonderland of powerful lactate‐based iodine catalysts. Unlike Alice's concern, these chiral iodine(I/III) compounds create the desired mirror‐image of each world with predictable stereocontrol. A state‐of‐the‐art description of the wonderland of powerful enantioselective iodine(I/III) catalysts is provided by the review of Flores et al. on pages 2–25 (A. Flores, E. Cots, J. Bergès, K. Muñiz, Adv. Synth. Catal . 2019, 361, 2–25; DOI: 10.1002/adsc.201800521 ).